The Movement of Postcolonialism by Kiai Sholeh Darat Against the Dutch Colonialism (Study of Social-Religious Decolonization in Java 19th and 20th Century) - Luthfi Maulana; Nurul Hak; Dudung Abdurrahman (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This research discusses the post-colonial movement of Kiah Sholeh Darat in fighting the Dutch colonial decolonization and imperialization at the end of the 19-20 centuries. Why is this research interesting to discuss? The resistance movement that is known by the general public only focuses on physical resistance. Meanwhile, Kiai Sholeh resisted through a cultural approach. Methodologically, this research is included in the Library research category with the aim of producing historical research studies based on postcolonial movements carried out by Kiai Sholeh Darat. From this it can be seen that the cultural movements of Kiai Sholeh Darat in the aftermath of the Java War in the 19th and early 20th centuries in Java can be seen as a post-colonial spirit and identity, because they show a tendency towards the spirit of decolonization towards the era of colonial regime domination in various lines of life of the Javanese people. The cultural movement of Kiai Sholeh Darat, which reflects the identity of the post-colonial movement, gave birth to a literacy movement which was manifested in publishing writings in the pegon script, also translating the Koran into Javanese as a form of resistance to the colonial project which attempted to present Java with Islam through the literacy movement and colonial philology; and carrying out the cadre of kiai who have a religious and nationalist spirit as well as conducting public education, in the form of da'wah from village to village or from city to city in Java.